Pharmacological investigations of newly synthesized oxazolones and imidazolones as COX-2 inhibitors - Iqra Saleem Naz Babari; Muhammad Islam; Hamid Saeed; Humaira Nadeem; Hassaan Anwer Rathore (Elsevier, 2024)
Oxazoles and Imidazoles are heterocyclic compounds with significant biological activities. The present study explores the pharmacological effects of some new oxazole and imidazole derivatives as potential COX-2 inhibitors. Docking studies of the compounds against targeted proteins COX-2 and TACE manifested good binding affinities for both the targets supporting their anti-inflammatory potential. Compounds (3F-A, 3F-B, N-A, N-B) were evaluated for in vivo anti-inflammatory effects by carrageenan-induced paw edema. Among all, compound N-A was found to be the most effective as it displayed most pronounced reduction in inflammation that was comparable to indomethacin. The in vivo tissue antioxidant activity was performed for estimation of the level of catalase, GSH, GST, and thiobarbituric acid in paw tissue. The results exhibited that targeted compounds improved the oxidative stress and restored the expression of enzymes. H &E staining revealed that aforesaid compounds displayed well-defined restoration of cellular damage. Compound NA exhibited maximum structural and functional preservation. Reduction in the expression of inflammatory markers was also analyzed by ELISA and maximum reduction in protein expression (COX-2 and TNF-a) was observed for compound N-B. Quantification of mRNA was done using PCR and a decrease in the expression of COX-2 mRNA level in treatment groups was depicted by all the new compounds but N-B showed maximum reduction in enzyme expression. All the results obtained from the present study have shown the significant anti-inflammatory potential of new compounds via the COX-2 inhibition pathway.